Berberine Exerts Anti-cancer Activity by Modulating Adenosine Monophosphate- Activated Protein Kinase (AMPK) and the Phosphatidylinositol 3-Kinase/ Protein Kinase B (PI3K/AKT) Signaling Pathways - Huang, Jin; Feng, Wei; Li, Shanshan; Tang, Huiling; Qin, Siru; Li, Wei; Gong, Yinan; Fang, Yuxin; Liu, Yangyang; Wang, Shenjun; Guo, Yi; Xu, Zhifang; et al. (Current Pharmaceutical Design, 2021)
Background: The antagonistic relationship between adenosine monophosphate-activated protein kinase (AMPK) and phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) signaling play a vital role in cancer development. The anti-cancer effects of berberine have been reported as a main component of the traditional Chinese medicine Rhizoma coptidis, although the roles of these signaling pathways in these effects have not been systematically reviewed. Methods: We searched the PubMed database for studies with keywords including [“berberine”] and [“tumor” or “cancer”] and [“AMPK”] or [“AKT”] published between January 2010 and July 2020, to elucidate the roles of the AMPK and PI3K/AKT pathways and their upstream and downstream targets in the anti-cancer effects of berberine. Results: The anti-cancer effects of berberine include inhibition of cancer cell proliferation, promotion of apoptosis and autophagy in cancer cells, and prevention of metastasis and angiogenesis. The mechanism of these effects involves multiple cell kinases and signaling pathways, including activation of AMPK and forkhead box transcription factor O3a (FOXO3a), accumulation of reactive oxygen species (ROS), and inhibition of the activity of PI3K/AKT, rapamycin (mTOR) and nuclear factor-ΚB (NF-ΚB). Most of these mechanisms converge on regulation of the balance of AMPK and PI3K/AKT signaling by berberine. Conclusion: This evidence supports the possibility that berberine is a promising anti-cancer natural product, with pharmaceutical potential in inhibiting cancer growth, metastasis and angiogenesis via multiple pathways, particularly by regulating the balance of AMPK and PI3K/AKT signaling. However, systematic preclinical studies are still required to provide scientific evidence for further clinical studies.
Keywords: AMPK